Single transition metal atom anchored on g-C3N4 as an electrocatalyst for nitrogen fixation: A computational study. (8th March 2023) - Zhang, Nan; Gao, Yaping; Ma, Lixia; Wang, Yuyang; Huang, Luo; Wei, Baoqiang; Xue, Yanzhong; Zhu, Houyu; Jiang, Ruibin
Abstract: Electrocatalytic nitrogen reduction reaction (NRR) provides a green and sustainable way to produce ammonia at ambient conditions. The key to realize highly efficient NRR is the catalysts. To design highly active electrocatalysts for NRR, the multistep mechanism involved in NRR must be clearly unraveled. Herein, single V atoms anchored on g-C3 N4 is identified to be an efficient electrocatalyst for NRR by screening single 3d transition metal (TM = Sc to Zn) atoms anchored by g-C3 N4 (TM@g-C3 N4 ) through density functional theory calculations. NRR takes place on V@g-C3 N4 preferentially through distal path with a relatively low limiting potential of −0.55 V. The outstanding NRR performance of V@g-C3 N4 is found from the peculiar electronic structure of V after anchored in the six-fold cavity of g-C3 N4 and the good transmitter role of V for electron transfer between Nx Hy species and g-C3 N4 . Moreover, the formation energy and dissolution potential indicate that V@g-C3 N4 is thermodynamically and electrochemically stable and the aggregation of V atoms is unfavorable thermodynamically, signifying that the synthesis of V@g-C3 N4 is feasible in experiments. Our work screens out a superior noble metal-free NRR electrocatalyst and will be helpful for the development of ambient artificial nitrogen fixation. Highlights: Single V atom anchored on g-C3 N4 is beneficial to the adsorption of N2 and the inhibition of hydrogen evolution reaction. The mechanism of high activity of V@g-C3 N4 nitrogen reduction reaction catalyst was systematically studied. The maximum stretching of N–N bond imply good catalytic activity, but it does not mean strong adsorption of N2 .